Praktik Employer Branding Untuk Retensi Karyawan di Pt XYZ - Rury Novianti M; Ahmad Badawi; Ahmad Azmy (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the effectiveness of employer branding in improving employee retention at PT XYZ, a multinational nickel mining company in Indonesia. It also seeks to identify practical strategies to address persistent turnover challenges in the extractive industry. Methodology/approach: The research uses a qualitative approach through Focus Group Discussions (FGDs) with five employees from both managerial and operational levels. Thematic analysis was conducted manually on the FGD transcripts. The analysis is supported by a literature review integrating Social Exchange Theory, Resource-Based View (RBV), and Psychological Contract Theory to frame the findings. Results/findings: The study identifies five core employer branding practices that significantly influence retention: (1) competitive compensation and risk allowances, (2) flexible work arrangements (e.g., Work from Home), (3) competency development programs, (4) transformational leadership, and (5) ESG (Environmental, Social, and Governance) integration. Major challenges include unclear compensation structures, heavy workloads, and lack of transparency in career development pathways. Conclusions: Employer branding strategies tailored to local culture and industry needs significantly enhance employee retention at PT XYZ. Although the study is specific to Indonesia’s nickel mining sector, the findings offer transferable insights for HRM practices in other extractive industries within developing economies. Limitations: The findings are context-specific and derived from a small sample. The qualitative design limits the ability to establish statistical relationships between variables. Contribution: This study contributes to HRM theory by proposing an integrated employer branding model and provides mining companies with actionable strategies to align global HR practices with local expectations, especially in resource-driven sectors.